2007
DOI: 10.1093/carcin/bgm231
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of citrus 5-hydroxy-3,6,7,8,3',4'-hexamethoxyflavone on 12-O-tetradecanoylphorbol 13-acetate-induced skin inflammation and tumor promotion in mice

Abstract: 5-Hydroxy-3,6,7,8,3',4'-hexamethoxyflavone (5-OH-HxMF), a polymethoxyflavone, is found exclusively in the Citrus genus, particularly in the peels of sweet orange. Herein, we report the first investigation of the inhibitory effects of 5-OH-HxMF on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in mouse skin. We found that the topical application of 5-OH-HxMF can effectively inhibit the transcriptional activation of iNOS and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…However, the mechanisms underlying its actions have yet to be well characterized. In addition, recent studies have shown that some hydroxylated PMFs have more potent biological activities including anti-cancer and anti-inflammatory activities than their PMF counterparts [21,24,25]. This information indicated the hydroxylated PMFs may possess greater potency for colon cancer chemoprevention.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the mechanisms underlying its actions have yet to be well characterized. In addition, recent studies have shown that some hydroxylated PMFs have more potent biological activities including anti-cancer and anti-inflammatory activities than their PMF counterparts [21,24,25]. This information indicated the hydroxylated PMFs may possess greater potency for colon cancer chemoprevention.…”
Section: Introductionmentioning
confidence: 97%
“…Among these, polymethoxyflavones (PMFs), particularly in the peel of sweet oranges (Citrus sinensis) and mandarin oranges (Citrus reticulate), have been demonstrated to have various biological activities including anti-carcinogenic, anti-inflammatory and antitumor activities [19,20]. Our pervious studies also reported that 5-hydroxy- 3,6,7,8,3 0 ,4 0 -hexamethoxyflavone isolated from sweet orange peel extract shows the inhibitory effects against TPA-induced skin inflammation and tumor promotion in mice [21]. The most known and studied citrus PMF, nobiletin, has been reported in inhibition of AOMinduced colonic ACF formation in male F344 rats [22,23].…”
Section: Introductionmentioning
confidence: 98%
“…Phytochemical studies of Citrus peels have led to identifying some metabolites including flavonoids [2,3], limonoids [4,5], and coumarins [6]. Polymethoxyflavones (PMFs) have attracted considerable attention as bioactive constituents in Citrus peels [2,7] owing to their antiinflammatory [8], anticarcinogenic [9], and antiatherogenic properties [10]. Besides, antioxidant [11,12] and antitumor properties [13] were also identified from the flavonoids of Citrus genus.…”
Section: Introductionmentioning
confidence: 99%
“…The major polyphenols present in orange peel are flavanone glycosides, polymethoxylated flavone aglycons, flavone glycosides and C-glycosylated flavones (Sawalha et al, 2009) and health benefit such as anti -inflammatory, anticarcinogenic, anti-viral, antioxidant, anti-thrombogenic and anti-atherogenic properties has been reported it (Middleton et al, 2000;Whitman et al, 2005;Lai et al, 2007;Li et al, 2009). TPC reported for coffee silverskin was higher that the value found in the literature 0.17 mg EGA/g sample (Jiménez-Zamora et al, 2015).…”
Section: Resultsmentioning
confidence: 73%